Comparison of three concentrations of ropivacaine in posterior quadratus lumborum block: A randomized clinical trial - Wen-Kao Huang; Zhao-Kai Lu; Fan Deng; Xing-Xia Chen; Xiao-Yu Zhuo; Ke-Xuan Liu; Wei-Feng Liu (Heliyon, 2024)
Background: A conclusive evidence regarding the optimal concentration and volume of local anesthetic for quadratus lumborum block is lacking. Methods: In this single-center, prospective, randomized, controlled study, 60 patients scheduled for laparoscopic colorectal surgery were randomly assigned to 3 different combinations of volume and concentration of ropivacaine (3 mg/kg) - Group 0.25%, Group 0.375% and Group 0.5%. All subjects received ultrasound-guided posterior quadratus lumborum block prior to the induction. The primary outcome was the complete sensory block rate of surgical site measured at 30 min after quadratus lumborum block, after extubation, at 12, 24, and 48 h after operation. Secondary outcomes were the changes in hemodynamic parameters before and after incision (ΔSBP, ΔDBP and ΔHR), postoperative pain score, the sufentanil consumption after surgery, length of stay and adverse reactions. Results: The sensory block rate of surgical site at 5 time points differed significantly among the three groups (P < 0.001). Both Group 0.375% (P < 0.001) and Group 0.5% (P < 0.001) had a higher sensory block rate than Group 0.25%, but no significant difference was observed between the former two. Group 0.375% and Group 0.5% had lower postoperative pain scores, lower sufentanil consumption after surgery and shorter length of stay. No statistical difference was observed in ΔSBP, ΔDBP, ΔHR and the incidence of adverse reactions. Conclusions: 0.375% and 0.5% ropivacaine in posterior quadratus lumborum block provide better sensory block of surgical site when compared to 0.25% in laparoscopic colorectal surgery. Trial registration number: Chinese Clinical Trials Registry (ChiCTR2100043949).